Analisis Partisipasi Masyarakat Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di UPPRD Johar Baru Jakarta Periode Tahun 2017-2019 - Fathimatuz Zahra; Novianita Rulandari (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Local taxes are one of the sources of local revenue, including for the Johar Baru Jakarta Tax and Retribution Service Unit (UPPRD), which relies on one of the sources of income from the land and building tax revenue for the Rural Urban sector (PBB-P2). This study aims to determine the level of participation and compliance level of taxpayers in paying PBB-P2, the obstacles that have been found and the efforts that have been made. The author uses primary and secondary data which are then analyzed using descriptive qualitative methods. This study found that within three years the level of community participation and level of adherence was quite effective. One of the main factors and efforts that have an impact on public participation as taxpayers, namely the level of knowledge of the taxpayers themselves about the importance of paying taxes, as well as the inactivity of the community as wp in providing information on changes to their tax objects and on building ownership so that the data registered with data is not updated. in the field. Suggestions for the future are to create a new UPPRD Johar official site to make it easier for the public as taxpayers to update their tax object data without requiring the public as taxpayers to report to the UPPRD office